From good social policies to interconnected anti-poverty policies : what we need to begin the transition - Trivelli, Carolina (2015)
"This paper has two objectives: First, to discuss the challenges and the potential of the possible interconnection between targeted social policies and production-oriented policies and programs, especially programs aimed at achieving sustained income generation in the poorest families or providing them with tools for successful inclusion in the financial system; and second, to explore the processes needed to implement these interconnections. We propose a road map that begins with pilot programs, which can become larger-scale social policies with broader coverage after a process of learning and adaptation. This model emerges from two recent experiences of targeted social policy in Peru: the Juntos-Haku Wiñay pilot and the financial inclusion pilot program for users of the Juntos CCT program." –Abstract.